An unexpected cause of residual renal function loss. Issue 4 (July 2020) - Soares, Elsa; Valério, Patricia; Abrantes, Catarina; Furtado, Teresa; Assunção, José; Vaz, Alvaro G
The residual renal function (RRF) in a peritoneal dialysis (PD) patient is clinically important because it contributes to dialytic adequacy, quality of life and mortality. We present the case of a patient in PD with a marked decrease in RRF. Even after the increase of dialysis, the patient maintained asthenia and anorexia, was prostrate and showed no improvement analytically. The study revealed hypothyroidism, iatrogenic due to the use of amiodarone. After suspension of the drug and replacement with levothyroxine, there was a normalization of thyroid function and recovery of RRF to baseline values. A thyroid dysfunction is associated with several changes in renal function, in most cases reversible after obtaining euthyroid state. The association between thyroid dysfunction and loss of RRF continues to be under-recognized. We should consider monitoring thyroid function annually as routine in this group of patients.